(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Benzylation of o-cresol with benzyl alcohol (Bz-OH) in presence of 94% H2SO4 as catalyst was studied statistically with a two-levels threefactored experimental design to study the effects of single factor and effects of their interactions on the yield of benzylated product. Reaction temperature, molar ratio of o-cresol to Bz-OH and amount of 94% H2SO4 were considered as the major variables. A mathematical model was derived to calculate the predicted yield of benzyl o-cresol as y = 0.419T+12.4055m+16.17w-0.0525Tm-2.606mw- 0.094Tw+0.0175Tmw-6.25; where, T = temperature (oC), m = o-cresol to Bz-OH molar ratio, w = amount of catalyst (% by wt. of o-cresol) and y = yield. The adequacy of the suggested model was checked up and the discrepancies between the experimental and calculated values did not exceed ± 0.79%. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10727 Bangladesh J. Sci. Ind. Res. 47(1), 137-142, 2012